(untitled) (Global Conference on Medical and Health Sciences, 2026)
In laparoscopic ventral hernioplasty, the method of mesh fixation largely determines the incidence of chronic postoperative pain and of mesh displacement with subsequent recurrence. Mechanical tackers are associated with fixation-related pain, which makes it necessary to improve reliable, low-morbidity fixation techniques.